Surface modification of Teflon® PFA with vacuum UV photo-oxidation - Dasilva, W.; Entenberg, A.; Kahn, B.; Debies, T.; Takacs, G. A.
Surface modification of poly(tetrafluoroethylene-co-perfluoropropyl vinyl ether)(PFA)with vacuum UV (VUV)photo-oxidation using radiation from excited Ar atoms downstream from an Ar microwave (MW)plasma shows: (1)an improvement in wettability as observed by water contactangle measurements; (2)surface roughening; (3)incorporation of oxygen as C=O, CF-O-CF2 and CF2-O-CF2 moieties and (4)enhancement of the CF-O-C n F2n+1 concentration. Adhesion measurements of Cu sputter coated onto the photo-oxidized PFA surface results in failure within the PFA (cohesive failure)and not at the Cu-PFA interface.
Keywords: SURFACE MODIFICATION; TEFLON+; PFA; COPPER, VUV; PHOTO-OXIDATION; COHESIVE FAILURE; ADHESION; AR MICROWAVE PLASMA